Agribusiness impact in a climate context: A hands-on crash course on tracking what matters - Nowak, Andreea C. (2024)
Impact measurement is not just about the numbers or about checking whether certain actions have been completed; it’s also about the story. The foundation of this story is the impact pathway framework. The impact pathway provides a structured process to map challenges agribusinesses aim to solve (pain points); solutions they implement to address these challenges, such as core business activities; results or immediate outcomes; and impacts – the broader, long-term changes. By framing impact as a story or pathway, agribusinesses can connect with stakeholders on a deeper level, showcasing not just what they do but why it matters.